United States’ Political Rights Values: Critiques of Human Rights Violations Towards Hispanic Americans - Purwitasari, Artie Indah (Jurnal Pemikiran Sosiologi, 2024)
This study examines the ongoing violations of political rights experienced by Hispanic Americans, despite the United States established democratic principles. It examines the impact of globalization on human rights issues, leading to the "othering" of Hispanic Americans by the United States government. The study uses Herbert Blumer's Symbolic Interactionism as a theoretical framework to analyze how meanings and interpretations influence the experiences and treatment of this excluded group. A thematic review of the current literature, utilizing a qualitative research methodology, uncovers a complex interaction of elements that contribute to these violations. The study examines the conflict of national interests, changing ethical norms, and the symbolic creation of "otherness" that rationalizes discriminatory behaviors. Research indicates that globalization, whilst fostering connection, may also intensify pre-existing inequities and generate novel forms of marginalization. The study indicates that the United States, as a global power, confronts a significant issue in aligning its democratic principles with its treatment of Hispanic Americans. It underscores the imperative for the US to reinforce its dedication to human rights and harmonize its policies with the tenets of inclusivity and equality for all citizens. This necessitates a thorough analysis of the symbolic mechanisms that sustain prejudice and a fresh commitment to protecting human rights in a worldwide context.